KONSELING PASTORAL: JEMBATAN PEMAHAMAN BUDAYA MAENGKET DALAM TEOLOGI KONTEKSTUAL - Frieska Putrima Tadung; Fernanda Frisky Palit; Gladys Masoara; Lira In Makanoneng; Julieva Angelia Takasihaeng (Institut Agama Kristen Negeri Manado, 2024)
Pastoral counseling serves as a crucial bridge for understanding Maengket culture within the framework of contextual theology. This research investigates the integration of the rich social and religious values of Maengket culture into contemporary counseling practices. Using a qualitative approach, the study reveals that incorporating local cultural elements into pastoral counseling not only enhances the spiritual bond between counselors and clients but also aids in preserving Minahasan cultural heritage amidst the forces of globalization. The findings indicate that contextual pastoral counseling offers a deeper understanding and greater relevance for both individuals and communities as they navigate modern life challenges. Furthermore, this approach reinforces social solidarity and care, which are fundamental aspects of pastoral practice within Minahasa society.